Upaya Meningkatkan Kompetensi Guru dalam Menyusun Modul Ajar Melalui Pelatihan di Kelompok Kerja Guru Agama Katolik Kulon Progo - Isdiyati Isdiyati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to expose the ability of teachers in compiling teaching modules through training activities. This study used action research methods developed by Kemis and Taggart. Each cycle includes activities, namely action plans, action execution, observation, and reflection. The subjects of the study were teachers who were members of the Catholic Teachers Working Group in Kulon Progo. The results showed that there was an increase in teachers' professional competence in preparing lesson plans. In the first cycle, the average score obtained was 59.55% in the sufficient category, increasing to 91.27% in the second cycle with the very good category. Training activities can improve the competence of teachers of the Kulon Progo Catholic Teacher Working Group in compiling teaching modules.